EVALUATION OF GREEN MANUFACTURING IMPLEMENTATION ON REGULATION, COSTS, AND KNOWLEDGE - Iggy Adbaidainy (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2021)
Introduction: This study aims to analyze whether there is motivation of knowledge, regulations, and costs on the effect of the application of Green Manufacturing. Part of green manufacturing has been implemented. However, its implementation is not easy for various reasons and it has not a significant effect on the industrial world from several sectors. Methods: Data collection methods include questionnaires and interviews. This study uses primary data obtained through direct respondents. The statistical analysis tool in this study uses SPSS.Results: Based on the results of data analysis and discussion, it shows that the knowledge variable has a positive effect on the motivation to implement green manufacturing. In addition, the second variable, namely regulation, also shows a positive effect on the motivation to implement green manufacturing. However, the third variable shows that costs have a negative effect on the motivation to implement green manufacturing.Conclusion and suggestion: The results of the analysis prove that the tempe business motivation in Ngawi on implementing green manufacturing tends to be low. This requires synergy between the government and tempe entrepreneurs to applicate the green manufacturing. For the government, there is a need some socialization regarding the application of green manufacturing so that your knowledge of the application of green manufacturing will increase.